2020
DOI: 10.3390/ma13194291
|View full text |Cite
|
Sign up to set email alerts
|

The Study on the Whole Stress–Strain Curves of Coral Fly Ash-Slag Alkali-Activated Concrete under Uniaxial Compression

Abstract: This study aimed to research the whole stress–strain curves of coral Fly Ash-Slag Alkali-Activated Concrete (CAAC) in different strength grades. Fly ash-slag alkali-activated concrete was used as cementing materials to produce coral aggregate concrete. A monotonic loading test was conducted on the prismatic specimens to obtain elastic modulus (Ec), Poisson’s ratio (μ) and the constitutive relationship of CAAC under uniaxial compression. When the strain of CAAC reached the maximum value, the specimen was split … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Subject focus [9,10,[19][20][21][22][11][12][13][14][15][16][17][18] Structural performance of ZCC [23, 24,33,[25][26][27][28][29][30][31][32] Mix design procedure [28,[34][35][36] Comprehensive review of the mixture design proportion and procedure [7,37,[46][47][48][49][38][39][40][41][42][43][44][45] Stress-strain characteristics [3,7,[54][55][56][57][58][59][60][61][62]…”
Section: Referencementioning
confidence: 99%
“…Subject focus [9,10,[19][20][21][22][11][12][13][14][15][16][17][18] Structural performance of ZCC [23, 24,33,[25][26][27][28][29][30][31][32] Mix design procedure [28,[34][35][36] Comprehensive review of the mixture design proportion and procedure [7,37,[46][47][48][49][38][39][40][41][42][43][44][45] Stress-strain characteristics [3,7,[54][55][56][57][58][59][60][61][62]…”
Section: Referencementioning
confidence: 99%
“…The research findings demonstrated the adverse effects of CFA on mortar workability and discouraged supporting its use in concrete manufacturing. In addition, Huailiang et al [32] investigated the stress-strain behavior of fly ash and slag alkali-activated concrete tested under uniaxial compression. Spontaneous failure of specimens was observed once they reached peak stress, which was more pronounced with the high-grade concrete mixes.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is an artificial material that is widely used for building infrastructure in civil engineering [ 1 ] and it is estimated that around 30 billion tons of concrete are produced worldwide every year [ 2 ]. However, concrete production requires large quantities of natural fine and coarse aggregates, as about 70% of the total volume of concrete is composed these of aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that bottom ash can be used as a mineral admixture for concrete after (1) grinding to increase its pozzolanic reactivity [8], (2) sieving to increase its fineness [9], (3) the addition of a superplasticizer to reduce its water absorption [10], or (4) putting it in a cement kiln as a raw material [11]. However, it is difficult to use raw bottom ash directly as a mineral admixture for concrete because its use generally decreases the workability of fresh concrete due to the angular grain texture [12] and bottom ash has a lower pozzolanic reactivity than fly ash due to its larger particle size [12].…”
Section: Introductionmentioning
confidence: 99%